Determining the Optimum Level of Production in Carpet Production Workshops of Iran Carpet Co Based on the Global Supply Chain - Sharifikheirabadi, Mohammadreza; Sharifikheirabadi, Amin; Sharifikheirabadi, Mehdi (ExcelingTech, 2019)
In a competitive world of today's business, companies and organizations, utilizing various types of technology and management science, are creating competitive advantages of knowledge management tools and optimizing organizational processes. One of the most important managerial sciences that has raised usefulness in this field is logistics and supply chain. Despite the progress of technology in the present era and the development of the production and consumption of machine-made carpets, the handmade carpet, due to its beauty, elegance, natural materials and its original and valuable designs, has kept its popularity and continued to exist despite its many problems in the cycle of production and exports, and the presence of rivals such as China, Pakistan and India. Proper supply chain performance plays a crucial role in the success of the organization. Therefore, it is essential to use an appropriate supply chain performance assessment system to continuously improve it. The purpose of this study is to analyze the operation of the reciprocating chain in accordance with the operational reference model of the supply chain. First identified, which includes the ability, SCOR five criteria are based on the reliability model, flexibility, accountability, cost and asset. The present research is considered as an applied research in terms of type of the objective. The research field is the workshops of Iran Carpet Company active in 2014. The statistical population of this research includes all the carpet production workshops covered by Iran Carpet Company. Based on two documentary and survey methods, the data required has been collected. The results indicate that in some carpet production workshops, the production capacity has been optimal.